Treatment of tongue cavernous haemangioma with direct puncture and sclerotization with ethanol - Šeruga, Tomaž (Radiology and oncology (Ljubljana), 2015)
Background. Haemangiomas of tongue are rare type of malformations. They can be treated mostly conservatively but in some cases they need more aggressive treatment with preoperative intra arterial embolization and surgical resection. Lesions of tongue that are localized superficially can also be treated with direct puncture and injection of sclerosing agent (absolute ethanol). Case report. We present a case of a 48 years old female patient, where we performed embolization of cavernous haemangioma with mixture of absolute ethanol and oil contrast. After the procedure the patient received analgetics and antioedematous therapy. After the sclerotization the planed surgery was abandoned. Control MRI examinations 6 and 12 months after the procedure showed only a small remnant of haemangioma and no signs of a larger relapse. Conclusion. In our case the direct puncture of haemangioma and sclerotherapy with ethanol proved to be a safe and effective method to achieve preoperative devascularization of the lesion. Direct puncture of the lesion is not limited by the anatomy of the vessels or vasospasm, which can occur during the intra-arterial approach.
Keywords: etanol; ethanol; hemangiom; jezik; kontrastno sredstvo; Language; punkcija; sklerotizacija; vaskularne nepravilnosti